Is there an increased risk of twinning after discontinuation of the oral contraceptive pill?. Issue 3 (September 1989) - Murphy, M F; Campbell, M J; Bone, M
Abstract : We investigated whether conception soon after cessation of use of oral contraceptives affects the chance of bearing twins. Unpublished data from a large sample survey of contraceptive practice in Scotland were used to derive oral contraceptive discontinuation rates by month over the decade 1972-82 and these were related to estimated monozygotic and dizygotic twin birth rates and proportions by month in Scotland from 1974-82, using regression techniques. The results provide some support for the hypothesis that there is an increased risk of conceiving monozygotic twins within a year of ceasing to use oral contraceptives.